Adsorption of HCN onto Copper@Copper-Oxide Core–Shell Nanoparticle Systems - Septimus H. Liang; Shiliang Wang; David B. Pedersen (Adsorption Science & Technology)
Copper compounds are widely used as impregnants that enhance the removal of HCN by carbon-based filter media. The reaction mechanism involved is poorly understood. In this study, we have followed the reaction of HCN with pristine copper, copper oxide (CuO and Cu 2 O) and copper@copperoxide (Cu@Cu 2 O) core–shell nanoparticles of well-defined size and composition. We have established a cooperative reaction mechanism where both the copper oxide shell and copper core are required for the chemisorption of HCN onto copper nanoparticle impregnants. The suitability of copper@copperoxide nanoparticles as impregnants for the removal of HCN in respirator canisters is discussed.